High-entropy alloy water electrolysis catalytic material and preparation method thereof
By using high-entropy alloy catalytic materials with sheet-like structures, the main components are Fe, Co, Ni, Cu and Mo, the problems of slow oxygen evolution reaction kinetics and high cost of precious metal catalysts in electrolytic water reactions are solved, and high catalytic performance and low-cost electrolytic hydrogen production technology are achieved.
Patent Information
- Application Number
- CN202411723537.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-28
AI Technical Summary
In the existing electrolytic water reaction, the kinetics of the oxygen evolution reaction occurring at the anode are relatively slow, resulting in the overpotential of decomposed water that is too high, affecting the electrolytic efficiency. The commonly used precious metal catalysts are costly and have few reserves, which limits the promotion and application of electrolytic water hydrogen production technology.
A high-entropy alloy with a sheet-like structure is used as an electrolytic water catalytic material, with its main components: Fe, Co, Ni, Cu and Mo. By accurately controlling the atomic percentage of the five elements and combining with the sheet-like structure design, the combination of high-entropy effect and catalytic activity is achieved.
It achieves efficient catalytic performance and low usage cost, promotes the promotion and application of electrolytic water hydrogen production technology, and improves the specific surface area and structural stability of the material.
Smart Images

Figure CN119615240A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water electrolysis catalytic materials, and in particular to a high entropy alloy water electrolysis catalytic material and a preparation method thereof. Background Art
[0002] Hydrogen production through water electrolysis is a relatively convenient method for producing hydrogen. The water electrolysis reaction includes the hydrogen evolution reaction at the cathode and the oxygen evolution reaction at the anode. The oxygen evolution reaction at the anode is a four-electron process with relatively slow kinetics, which causes the overpotential of water decomposition to be too high, affecting the electrolysis efficiency. Therefore, the water electrolysis reaction requires the use of an efficient catalyst to accelerate the oxygen evolution reaction process in order to improve the efficiency of hydrogen production.
[0003] At present, the commonly used catalysts for water electrolysis reactions are still precious metal materials such as Pt, Au, Ru, and Ir. Although precious metal materials have high catalytic performance, they are expensive and have scarce reserves, which seriously limits the promotion and application of water electrolysis hydrogen production technology. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art. The present invention provides a high entropy alloy water electrolysis catalytic material and a preparation method thereof. By using a high entropy alloy with a flaky structure as the water electrolysis catalytic material, the main components of which are Fe, Co, Ni, Cu and Mo, not only can high catalytic performance be provided, but also the use cost can be effectively reduced, which is conducive to promoting the popularization and application of water electrolysis hydrogen production technology.
[0005] The present invention provides a high entropy alloy water electrolysis catalytic material, wherein the high entropy alloy water electrolysis catalytic material is a sheet structure, and the main component of the sheet structure is Fe a Co b Ni c Cu x Mo y , calculated in atomic percentage, a+b+c+x+y=1, 60at%≤a+b+c≤at90%, 10at%≤x+y≤40at%, 20at%≤a≤40at%, 20at%≤b≤40at%, 10at%≤c≤20at%, 5at%≤x≤35at%, 5at%≤y≤35at%.
[0006] Specifically, a is 30 at %, b is 30 at %, c is 15 at %, x is 15 at %, and y is 10 at %.
[0007] The present invention also provides a method for preparing a high entropy alloy water electrolysis catalytic material, comprising the following steps:
[0008] S1. According to Fe a Cob Ni c Cu x Mo y According to the atomic ratio of each element in the raw material, metal particles of Fe, Co, Ni, Cu and Mo are weighed respectively and mixed evenly to obtain a mixed metal raw material;
[0009] S2, placing the mixed metal raw material in a vacuum induction melting furnace and repeatedly melting it 3 to 6 times, and injecting it into a water-cooled copper mold to obtain a high entropy alloy ingot;
[0010] S3, taking a preset number of the high entropy alloy ingots and hot-rolling them into high entropy alloy bars, and taking a preset number of the high entropy alloy ingots and crushing them into high entropy alloy scraps;
[0011] S4, taking at least three of the high entropy alloy strips and winding them into a high entropy alloy rope, burying the high entropy alloy rope in the high entropy alloy scraps, heating them until they are melted into one, and obtaining a forging rough blank;
[0012] S5, repeatedly heating and forging the forged rough blank to form a high entropy alloy sheet;
[0013] S6. Soaking the high entropy alloy sheet in an oxidizing solution for 5 to 10 minutes to obtain a high entropy alloy water electrolysis catalytic material.
[0014] Specifically, in step S1, the diameter of the metal particles is less than or equal to 5 mm.
[0015] Specifically, in step S2, the smelting parameters include:
[0016] Before smelting, the vacuum range of the vacuum induction melting furnace is controlled to be 3.0×10 -2 ~6.0×10 -2 Pa;
[0017] During smelting, 50-60 kPa of nitrogen is filled into the vacuum induction melting furnace as a protective atmosphere;
[0018] During smelting, the medium frequency range of the vacuum induction melting furnace is controlled to be 1500-2500 Hz;
[0019] The smelting time is controlled between 1 and 3 minutes.
[0020] Specifically, in step S3, the diameter of the high entropy alloy strip is in the range of 3 to 6 mm, and the particle size of the high entropy alloy debris is in the range of 0.1 to 0.5 mm.
[0021] Specifically, in step S4, the mass ratio of the high entropy alloy rope to the high entropy alloy scraps is 1:1 to 2.5.
[0022] Specifically, in step S5, the thickness of the high entropy alloy sheet is in the range of 3 to 5 mm, the length of the high entropy alloy sheet is in the range of 10 to 20 cm, and the width of the high entropy alloy sheet is in the range of 7 to 15 cm.
[0023] Specifically, before step S6, the method further includes:
[0024] The high entropy alloy sheet is forged to form a plurality of pits on the surface of the high entropy alloy sheet.
[0025] Specifically, in step S6, the oxidizing solution is an acidic potassium permanganate solution or an acidic potassium dichromate solution.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The high entropy alloy water electrolysis catalytic material of the present invention mainly comprises Fe, Co, Ni, Cu and Mo, has lower use cost than precious metal materials such as Pt, Au, Ru and Ir, and is conducive to promoting the popularization and application of water electrolysis hydrogen production technology; moreover, by accurately controlling the atomic percentages of the five elements Fe, Co, Ni, Cu and Mo, an effective combination of high entropy effect and catalytic activity is achieved, ensuring that the material has high catalytic performance and high structural stability; at the same time, the sheet structure design is adopted to further increase the specific surface area of the material, provide more active sites, and further improve the catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 It is a schematic flow chart of a method for preparing a high entropy alloy water electrolysis catalytic material in an embodiment of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The present invention provides a high entropy alloy water electrolysis catalytic material, wherein the high entropy alloy water electrolysis catalytic material is a sheet structure, and the main component of the sheet structure is Fea Co b Ni c Cu x Mo y , calculated in atomic percentage, a+b+c+x+y=1, 60at%≤a+b+c≤at90%, 10at%≤x+y≤40at%, 20at%≤a≤40at%, 20at%≤b≤40at%, 10at%≤c≤20at%, 5at%≤x≤35at%, 5at%≤y≤35at%.
[0032] The high entropy alloy water electrolysis catalytic material of the present invention mainly comprises Fe, Co, Ni, Cu and Mo. Fe, Co and Ni are basic components, which can provide good intrinsic catalytic activity, and the introduction of Cu and Mo further optimizes the electronic structure of the catalytic material. Fe, Co, Ni, Cu and Mo are all non-precious metal materials, and the use cost is lower than that of precious metal materials such as Pt, Au, Ru and Ir, which is conducive to promoting the popularization and application of water electrolysis hydrogen production technology; moreover, by accurately controlling the atomic percentage of the five elements of Fe, Co, Ni, Cu and Mo, an effective combination of high entropy effect and catalytic activity is achieved, ensuring that it has high catalytic performance and high structural stability; at the same time, the use of a sheet structure design further increases the specific surface area of the material, provides more active sites, and further improves its catalytic performance.
[0033] In some specific embodiments, a is 30 at%, b is 30 at%, c is 15 at%, x is 15 at%, and y is 10 at%. The Fe and Co contents are each 30 at%, which can form a stable skeleton in the sheet structure, providing good mechanical strength and electron transmission capacity; the Ni content is 15 at%, which can form a synergistic effect with Fe and Co to further enhance the catalytic activity of the catalytic material; Cu (15 at%) and Mo (10 at%) as auxiliary elements can be distributed on the surface or subsurface of the sheet structure, adjust the local electronic structure, and optimize the desorption process of hydrogen or oxygen.
[0034] The present invention also provides a method for preparing a high entropy alloy water electrolysis catalytic material. Figure 1 The schematic diagram of the process for preparing the high entropy alloy water electrolysis catalytic material in the embodiment of the present invention is shown, comprising the following steps:
[0035] S1. According to Fe a Co b Ni c Cu x Mo y According to the atomic ratio of each element in the raw material, metal particles of Fe, Co, Ni, Cu and Mo are weighed respectively and mixed evenly to obtain a mixed metal raw material;
[0036] By accurately weighing each metal particle and mixing them evenly, a foundation is laid for the subsequent smelting of the mixed metal raw materials, which is beneficial to improving the uniformity of the smelting of the mixed metal raw materials.
[0037] In some specific embodiments, the diameter of the metal particles is less than or equal to 5 mm, which helps to improve the uniformity of the metal particles during mixing on the one hand, and helps to reduce the difficulty of subsequent smelting and improve the dispersion of various metal elements during smelting on the other hand.
[0038] Specifically, the diameter of the metal particles can be controlled at 1 mm, 2 mm, 3 mm, 4 mm or 5 mm; preferably, the diameter of the metal particles is 1 mm. The smaller the diameter of the metal particles, the easier it is to mix evenly and the better the dispersibility during smelting.
[0039] S2, placing the mixed metal raw material in a vacuum induction melting furnace and repeatedly melting it 3 to 6 times, and injecting it into a water-cooled copper mold to obtain a high entropy alloy ingot;
[0040] After the vacuum induction melting furnace melts the mixed metal raw materials into molten metal, it will produce electromagnetic stirring on the molten metal, which can accelerate the physical and chemical reaction rate during the smelting process; it can also make the composition of the molten metal liquid uniform; it can also make the temperature of the molten metal tend to be consistent, and promote the complete completion of the reaction during smelting; moreover, the result of electromagnetic stirring overcomes the effect of the static pressure of the molten metal itself, and can turn the molten bubbles in the deep to the surface of the liquid, which is convenient for gas discharge and reduces the gas inclusion content of the alloy.
[0041] Through multiple smelting, the metal elements can be fully dispersed, the defects of the high entropy alloy ingot can be reduced, and the crystal structure of the high entropy alloy ingot can be optimized. Specifically, the smelting can be performed 3, 4, 5 or 6 times. After smelting for more than 6 times, the crystal structure of the high entropy alloy ingot is basically stable, and continuing smelting will increase unnecessary energy consumption and production costs.
[0042] In some specific embodiments, the smelting parameters include:
[0043] Before smelting, the vacuum range of the vacuum induction melting furnace is controlled to be 3.0×10 -2 ~6.0×10 -2 Pa, which can effectively exhaust the air in the vacuum induction melting furnace, thereby reducing the influence of gas impurities during the melting process, thereby improving the purity of the alloy; preferably, the vacuum range of the vacuum induction melting furnace is controlled to 4.0×10 -2 ~5.0×10 -2 Pa, which is beneficial to reducing the workload of the vacuum pump.
[0044] During smelting, 50-60 kPa of nitrogen is filled into the vacuum induction melting furnace as a protective atmosphere, which can prevent oxidation reactions during high-temperature smelting and ensure the stability of the alloy components; preferably, 55 kPa of nitrogen is filled into the vacuum induction melting furnace, which provides protection while not affecting the exhaust of gas from the molten metal.
[0045] During smelting, the medium frequency range of the vacuum induction melting furnace is controlled to be 1500-2500 Hz, which helps to achieve rapid and sufficient melting of the mixed metal raw materials; preferably, the medium frequency range of the vacuum induction melting furnace is controlled to be 2000 Hz, which can produce a good electromagnetic stirring effect.
[0046] The smelting time is controlled within 1 to 3 minutes, which is sufficient to ensure that the metal raw materials are fully melted and evenly mixed; preferably, the smelting time is controlled within 2 minutes, which has good coordination with other process parameters.
[0047] S3, taking a preset number of the high entropy alloy ingots and hot-rolling them into high entropy alloy bars, and taking a preset number of the high entropy alloy ingots and crushing them into high entropy alloy scraps;
[0048] Through hot rolling and crushing, high entropy alloy bars and chips are prepared respectively, providing raw materials for subsequent processing.
[0049] In some specific embodiments, the diameter of the high entropy alloy strip is in the range of 3 to 6 mm, and the thickness is appropriate, so that the high entropy alloy strip has appropriate strength and flexibility. When the diameter of the high entropy alloy strip is less than 3 mm, the high entropy alloy strip is too thin and weak, and it is easy to break or deform during the winding process; when the diameter of the high entropy alloy strip is greater than 6 mm, the high entropy alloy strip is too rough and hard, and it is difficult to perform an effective winding operation.
[0050] Preferably, the diameter of the high entropy alloy strip is 4 mm, which has a good effect of being wound into a high entropy alloy rope, and the strip morphology is easy to retain during subsequent forging.
[0051] In some specific embodiments, the particle size range of the high entropy alloy debris is 0.1 to 0.5 mm. When the particle size of the high entropy alloy debris is less than 0.1 mm, the high entropy alloy debris is too small, the processing difficulty is high, and it is easy to produce splashing or oxidation during the crushing process, affecting the purity and performance of the high entropy alloy; when the particle size of the high entropy alloy debris is greater than 0.5 mm, the high entropy alloy debris cannot quickly penetrate into the gaps of the high entropy alloy rope during the subsequent melting process, which is easy to affect the structural strength of the forged rough blank; the particle size range of 0.1 to 0.5 mm can ensure that the debris is easy to melt again during the smelting process, and can also effectively penetrate into the gaps of the high entropy alloy rope to form a good bonding effect.
[0052] Preferably, the particle size range of the high entropy alloy debris is 0.3-0.4 mm, which is easy to produce. When the high entropy alloy ingot is crushed, the particle size of most of the debris falls within this range.
[0053] S4, taking at least three of the high entropy alloy strips and winding them into a high entropy alloy rope, burying the high entropy alloy rope in the high entropy alloy scraps, heating them until they are melted into one, and obtaining a forging rough blank;
[0054] The high-entropy alloy debris will first melt and fill the gaps in the high-entropy alloy rope to form a forging rough blank with a special structure. When the high-entropy alloy sheet is subsequently made, special patterns will be formed, thereby introducing certain surface defects and grain boundaries, which can increase the catalytic active sites on the surface of the high-entropy alloy sheet.
[0055] In some specific embodiments, the mass ratio of the high entropy alloy rope to the high entropy alloy scraps is 1:1-2.5, and the amount of high entropy alloy scraps used is appropriate, which ensures that the high entropy alloy scraps can fully fill the gaps in the high entropy alloy rope after melting, and avoids excessive high entropy alloy scraps affecting the structural strength of the forged rough blank.
[0056] Specifically, different specific ratios such as 1:1, 1:1.5, 1:2 or 1:2.5 can be selected. As the proportion of high entropy alloy debris increases, the structural strength of the obtained forging rough blank is higher, and it is less likely to fall apart during subsequent forging.
[0057] In some specific embodiments, the heating temperature of the high entropy alloy scraps and the high entropy alloy rope is controlled to be 1400-1600° C., so that the high entropy alloy scraps can be fully melted while the high entropy alloy rope still maintains its original structural form.
[0058] Specifically, different specific temperatures such as 1400°C, 1500°C or 1600°C may be selected. As the heating temperature increases, the degree of fusion between the high entropy alloy debris and the high entropy alloy rope increases.
[0059] In some specific embodiments, 6 high-entropy alloy strips are taken and wound into a high-entropy alloy rope, and the high-entropy alloy rope is wound into a disk and buried in the high-entropy alloy debris, and then heated to melt into one, to obtain a block-shaped forging rough blank; such a forging rough blank has higher strength and larger area, which is convenient for subsequent forging of large high-entropy alloy sheets.
[0060] S5, repeatedly heating and forging the forged rough blank to form a high entropy alloy sheet;
[0061] By heating and forging the forged rough blank into a high-entropy alloy sheet, the texture of the high-entropy alloy rope can be well preserved, and certain surface defects and grain boundaries can be introduced into the high-entropy alloy sheet, which can increase the catalytic active sites on the surface of the high-entropy alloy sheet.
[0062] In some specific embodiments, the thickness of the high entropy alloy sheet ranges from 3 to 5 mm, which can ensure that the high entropy alloy sheet has sufficient mechanical strength; preferably, the thickness of the high entropy alloy sheet is 4 mm, which can maintain good mechanical properties without affecting electron transfer due to excessive thickness.
[0063] The length of the high entropy alloy sheet ranges from 10 to 20 cm, and the width of the high entropy alloy sheet ranges from 7 to 15 cm, which can provide sufficient reaction area and is also convenient for practical application and operation; preferably, the length of the high entropy alloy sheet is 15 cm, and the width of the high entropy alloy sheet is 11 cm, which can achieve a balance between ensuring sufficient catalytic reaction area and facilitating preparation and installation.
[0064] Specifically, the forging rough blank can be forged into a metal sheet of 3 to 5 mm, and then cut into a high-entropy alloy sheet of 10 to 20 cm in length and 7 to 15 cm in width, which is convenient and quick.
[0065] S6. Soaking the high entropy alloy sheet in an oxidizing solution for 5 to 10 minutes to obtain a high entropy alloy water electrolysis catalytic material.
[0066] Using an oxidizing solution to corrode and oxidize the surface of the high entropy alloy sheet can not only optimize the surface morphology of the high entropy alloy sheet, but also form metal oxides on the surface of the high entropy alloy sheet. The metal elements and metal oxides on the high entropy alloy sheet can produce a synergistic effect, thereby achieving the effective construction of active sites on the surface of the high entropy alloy sheet.
[0067] In some specific embodiments, the oxidizing solution is an acidic potassium permanganate solution or an acidic potassium dichromate solution, which can effectively corrode and oxidize the surface of the high entropy alloy sheet.
[0068] Specifically, the concentration range of the acidic potassium permanganate solution is 1-2wt%, the pH value range of the acidic potassium permanganate solution is 2-4, and it has good corrosion and oxidation effects; preferably, the concentration of the acidic potassium permanganate solution is 1.5wt%, the pH value of the acidic potassium permanganate solution is 3, and it has good corrosion and oxidation effects on high entropy alloy sheets.
[0069] The concentration range of the acidic potassium dichromate solution is 5-6wt%, the pH value range of the acidic potassium dichromate solution is 1-5, and it has good corrosion and oxidation effects; preferably, the concentration of the acidic potassium dichromate solution is 5.5wt%, the pH value of the acidic potassium dichromate solution is 3, and it has good corrosion and oxidation effects on high entropy alloy sheets.
[0070] In some specific embodiments, before the high entropy alloy sheet is immersed in the oxidizing solution, the process further includes: forging the high entropy alloy sheet to form a plurality of pits on the surface of the high entropy alloy sheet. By forging the high entropy alloy sheet to form pits, the specific surface area of the high entropy alloy sheet can be increased, providing more active sites; moreover, these pit structures can increase the contact area between water and the surface of the catalytic material, which is beneficial to the electrolysis of water; at the same time, the pit structure will produce a local electric field enhancement effect, further promoting the electrolysis of water.
[0071] In addition, the pit structure can also change the electronic structure of the surface of the high entropy alloy sheet and affect its catalytic performance. By regulating the number and distribution of pits, the catalytic activity of the high entropy alloy sheet can be optimized. This technical means, combined with the subsequent oxidizing solution immersion step, can further optimize the morphology and chemical composition of the catalytic material surface, thereby improving the overall performance of the high entropy alloy water electrolysis catalytic material.
[0072] Specifically, a mechanical press can be used for forging, and the depth and density of the pits can be adjusted by controlling the pressure and the number of forging times; a mold with a specific texture can also be used for embossing, so that regularly distributed pits can be formed on the surface of the high-entropy alloy sheet; an ultrasonic-assisted forging method can also be used to use the vibration effect of ultrasonic waves to form a microscopic-scale pit structure on the surface of the high-entropy alloy sheet.
[0073] Furthermore, the depth of the pits can be controlled within the range of 500-1000 μm, the diameter within the range of 3000-5000 μm, and the density of the pits can be controlled within the range of 4-9 / cm 2 The selection of these parameters will directly affect the specific surface area and the number of active sites of the material, thereby affecting its catalytic performance.
[0074] In the preparation method of the high entropy alloy water electrolysis catalytic material of the present invention, by accurately controlling the high entropy alloy composition, optimizing the preparation process and surface treatment, a high entropy alloy catalytic material with a specific composition and structure can be prepared, which can effectively increase the active sites on the surface of the high entropy alloy water electrolysis catalytic material, thereby significantly improving the catalytic efficiency in the water electrolysis process.
[0075] The above is a detailed introduction to a high entropy alloy water electrolysis catalytic material and a preparation method thereof provided in an embodiment of the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea; at the same time, for a person skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A high entropy alloy water electrolysis catalytic material, characterized in that: The high entropy alloy water electrolysis catalytic material is a sheet structure, and the main component of the sheet structure is Fe a Co b Ni c Cu x Mo y , calculated in atomic percentage, a+b+c+x+y=1, 60at%≤a+b+c≤at90%, 10at%≤x+y≤40at%, 20at%≤a≤40at%, 20at%≤b≤40at%, 10at%≤c≤20at%, 5at%≤x≤35at%, 5at%≤y≤35at%.
2. The high entropy alloy water electrolysis catalytic material according to claim 1, characterized in that: a is 30 at %, b is 30 at %, c is 15 at %, x is 15 at %, and y is 10 at %.
3. A method for preparing a high entropy alloy water electrolysis catalytic material as claimed in claim 1, characterized in that: The following steps are involved: S1. According to Fe a Co b Ni c Cu x Mo y According to the atomic ratio of each element in the raw material, metal particles of Fe, Co, Ni, Cu and Mo are weighed respectively and mixed evenly to obtain a mixed metal raw material; S2, placing the mixed metal raw material in a vacuum induction melting furnace and repeatedly melting it 3 to 6 times, and injecting it into a water-cooled copper mold to obtain a high entropy alloy ingot; S3, taking a preset number of the high entropy alloy ingots and hot-rolling them into high entropy alloy bars, and taking a preset number of the high entropy alloy ingots and crushing them into high entropy alloy scraps; S4, taking at least three of the high entropy alloy strips and winding them into a high entropy alloy rope, burying the high entropy alloy rope in the high entropy alloy scraps, heating them until they are melted into one, and obtaining a forging rough blank; S5, repeatedly heating and forging the forged rough blank to form a high entropy alloy sheet; S6. Soaking the high entropy alloy sheet in an oxidizing solution for 5 to 10 minutes to obtain a high entropy alloy water electrolysis catalytic material.
4. The method for preparing a high entropy alloy water electrolysis catalytic material as claimed in claim 3, characterized in that: In step S1 , the diameter of the metal particles is less than or equal to 5 mm.
5. The method for preparing a high entropy alloy water electrolysis catalytic material as claimed in claim 3, characterized in that: In step S2, the smelting parameters include: Before smelting, the vacuum range of the vacuum induction melting furnace is controlled to be 3.0×10 -2 ~6.0×10 -2 Pa; During smelting, 50-60 kPa of nitrogen is filled into the vacuum induction melting furnace as a protective atmosphere; During smelting, the medium frequency range of the vacuum induction melting furnace is controlled to be 1500-2500 Hz; The smelting time is controlled within 1 to 3 minutes.
6. The method for preparing a high entropy alloy water electrolysis catalytic material as claimed in claim 3, characterized in that: In step S3, the diameter of the high entropy alloy strip is in the range of 3 to 6 mm, and the particle size of the high entropy alloy debris is in the range of 0.1 to 0.5 mm.
7. The method for preparing a high entropy alloy water electrolysis catalytic material as claimed in claim 3, characterized in that: In step S4, the mass ratio of the high entropy alloy rope to the high entropy alloy scraps is 1:1 to 2.
5.
8. The method for preparing a high entropy alloy water electrolysis catalytic material as claimed in claim 3, characterized in that: In step S5, the thickness of the high entropy alloy sheet is in the range of 3 to 5 mm, the length of the high entropy alloy sheet is in the range of 10 to 20 cm, and the width of the high entropy alloy sheet is in the range of 7 to 15 cm.
9. The method for preparing a high entropy alloy water electrolysis catalytic material as claimed in claim 3, characterized in that: Before step S6, the method further includes: The high entropy alloy sheet is forged to form a plurality of pits on the surface of the high entropy alloy sheet.
10. The method for preparing a high entropy alloy water electrolysis catalytic material according to claim 3, characterized in that: In step S6, the oxidizing solution is an acidic potassium permanganate solution or an acidic potassium dichromate solution.
Citation Information
Patent Citations
Nano-porous Fe-based amorphous alloy, preparing method and application to oxygen evolution catalytic electrode
CN106222584A
A nanometer porous high-entropy alloy electrode, a preparing method thereof and applications of the electrode
CN107587158A
High-activity Mn-rich high-entropy alloy water electrolysis catalytic material and preparation method thereof
CN113122875A
Six-element high-entropy foam for hydrogen production through hydrolysis and preparation method of six-element high-entropy foam
CN114836780A
Nano porous high-entropy alloy catalyst and preparation method thereof
CN117344325A